Alpha-protein kinase 3 (ALPK3) truncating variants cause an autosomal dominant form of hypertrophic cardiomyopathy. (14th October 2021) - Rocha Lopes, L; Hernandez, S G; Lorenzini, M; Futema, M; Chumakova, O; Villacorta, E; Garcia-Pavia, P; Bilbao, R; Sandin-Fuentes, M; Pinilla, J G; Rasmussen, T B; Revilla-Marti, P; et al.
Abstract: Background: More than half of hypertrophic cardiomyopathy (HCM) remains genetically unsolved. ALPK3 truncating variants (ALPK3tv) have been described as a cause of autosomal recessive cardiomyopathy in a small number of paediatric cases, but the pathogenicity in heterozygosity as a possible cause of autosomal dominant HCM is unknown. Aims: To determine the frequency of heterozygous ALPK3tv in patients with HCM and to confirm their pathogenicity by means of burden testing in independent cohorts, family co-segregation studies, and functional analysis of an allelic series of ALPK3tv using human embryonic stem cell-cardiomyocytes (hESC-CM). Phenotype was compared with a cohort of 1679 genotyped HCM patients. Methods and results: In a discovery cohort of 770 index patients with HCM, 12 (1.56%) were heterozygous for ALPK3tv, odds ratio (OR) 16.01 (95% confidence interval (95% CI): 7.89 to 29.74, p<8.36e-11), compared to the Genome Aggregation Database (gnomAD) population. In a validation cohort of 2047 HCM probands, 32 (1.56%) carried heterozygous ALPK3tv, OR 16.17 (95% CI: 10.31 to 24.87; p<2.2e-16, compared to gnomAD). Combined logarithm of odds score in 7 families with ALPK3tv was 2.99. In comparison with a large cohort of genotyped HCM patients, the phenotype of 51 HCM patients with ALPK3tv (probands and relatives) was characterised by a higher prevalence of apical/concentric patterns of hypertrophy (60%) compared to both sarcomere-positives or negatives (p<0.001 overall), with the age at diagnosis (56±16ys) and maximum wall thickness (18±4mm) similar to sarcomere-negatives and LV systolic impairment at baseline (6%) and non-sustained ventricular tachycardia (31%) similar to sarcomere-positives. Short PR (10%, p=0.009 overall) and extensive fibrosis>15% of LV segments (49%) were distinctive features. During follow-up (5.3±5.7 years), 4 (9%) patients died of heart failure or had cardiac transplantation (p=0.012 vs sarcomere-negatives and p=0.425 vs sarcomere-positives). Analysis of hESC-CM showed that ALPK3 heterozygotes had phenotypic characteristics of HCM, including increased contractile force and delayed membrane repolarization. Conclusions: Heterozygous ALPK3tv are pathogenic and segregate with a characteristic HCM phenotype. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): MRC UK, UCLH BRC